Performance Analysis of the SiJaspro Application as a Tool for Physical Fitness Testing at Jasdam II Sriwijaya - Huda, Nurul; Halim, R. M. Nasrul; Udariansyah, Devi; Dianto, Tri Agung (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Technological advances have affected many areas of daily life, including sports. Calculations are essential to achieving physical exercise goals. To meet this need, Jasdam II Sriwijaya has created an application called SiJaspro that supports training by offering important data and calculations. This application is designed to assess fitness scores, provide training materials, and provide information related to Jasdam II Sriwijaya. Although this application has just been launched, it already has bugs on some pages, has difficulty displaying user data correctly, and is only compatible with Android devices. The PIECES method—Performance, Information and Data, Economics, Control and Security, Efficiency, and Service—has been applied to assess the performance of the application in this study. This analysis aims to assess the performance of the application in Jasdam II Sriwijaya and evaluate it against the objectives that have been set. GTMetrix is used for speed and performance testing, and Google Transparency Report is used for security testing.